Financial Well-Being among Fisabilillah Zakat Recipients in Public Universities - Amni Mohd Adnan; Azwan Abdullah; Mohd Zulkifli Muhammad (Universiti Sains Islam Malaysia, 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 22 Issue 2 Page (1–13)